Restaurant customers’ food leftover reduction intention derived from nature connection and biospheric values: A comparison between men and women - Kim, Wansoo; Che, Chen; Jeong, Chul (Frontiers in Psychology, 2023)
As the COVID-19 pandemic extends over a long period of time, the WFP (World Food Programme) estimated that food insecurity would take place in the near future. Previous studies focused on various kinds of interventions for food waste prevention. Surprisingly, however, research tackling consumer attitudes and behaviors as a way to reduce food waste is still rare. To fill this gap in the literature, this study examined the antecedent roles of restaurant customers’ nature connection and biospheric values in fostering their food leftover reduction intention through environmental self-identity and sense of obligation to reduce food leftover. In addition, the moderating effects of gender were tested on all the relationships in our conceptual model. A quantitative approach with an online survey for restaurant customers was adopted. Structural equation modeling was adopted to analyze the data. Through confirmatory factor analyses, the adequate reliability and validity of the measures were established. All the relationships between the constructs were found to be significant, supporting the hypotheses. In other words, the restaurant customers’ nature connection and biospheric values were found to eventually induce the customers’ food leftover reduction intention. In addition, in terms of the moderating effect, the male customers’ nature connection more strongly increased their biospheric values than the female customers’ case. The findings of this study revealed how restaurant customers’ food leftover reduction intention is formed through their feeling of oneness with nature and biospheric values. Given that consumer behavior has been recognized as a major driver of restaurant food waste, the findings of this study provide useful insights to restauranteurs and policymakers for the health of society and people in it. It was especially true for men in that their feeling of oneness with nature significantly influences their biospheric values more than women’s.